Study on the application of preoperative three-dimensional CT angiography of perigastric arteries in laparoscopic radical gastrectomy - Peng Liu; Meng Wei; Danping Sun; Xin Zhong; Yize Liang; Jun Ouyang; Yuan Zhang; Wenbin Yu (Scientific Reports, 2022)
Abstract To investigate the clinical value and significance of preoperative three-dimensional computerized tomography angiography (CTA) in laparoscopic radical gastrectomy for gastric cancer. The clinical data were analyzed retrospectively from 214 gastric cancer patients. We grouped according to whether to perform CTA, and we compared and analyzed the difference of the data between the two groups. The perigastric arteries were classified according to CTA images of patients in the CTA group. The celiac trunk was classified according to Adachi classification: Type I (118/125, 94.4%), Type II (3/125, 2.4%), Type III (0/125, 0%), Type IV (1/125, 0.8%), Type V (2/125, 1.6%), Type VI (1/125, 0.8%). Hepatic artery classification was performed according to Hiatt classification: Type I (102/125, 81.6%), Type II (9/125, 7.2%), Type III (6/125, 4.8%), Type IV (2/125, 1.6%), Type V (3/125, 2.4%), Type VI (0, 0%), Others (3/125, 2.4%). And this study combined vascular anatomy and surgical risk to establish a new splenic artery classification model. In comparison, the operation time, first exhaust time, and estimated blood loss in the CTA group were significantly lower than those in the non-CTA group. In addition, the blood loss in the CTA group combined with ICG (Indocyanine Green) labeled fluorescence laparoscopy was significantly less than that in the group without ICG labeled. Preoperative CTA could objectively evaluate patients' vascular route and variation and then help us avoid or decrease the risk of vascular injury and bleeding. When combined with ICG labeled fluorescence laparoscopy, it could further reduce the risk of iatrogenic injury during the operation and improve postoperative recovery.